1996
DOI: 10.1136/bmj.312.7029.485
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners' management of acute back pain: a survey of reported practice compared with clinical guidelines

Abstract: Objective-To compare general practitioners' reported management of acute back pain with "evidence based" guidelines for its management.Design-Confidential postal questionnaire. A minority performed manipulation (201/6) or acupuncture (6%). One third rated their satisfaction with management ofback pain as 4 out of 10 or less. Conclusions-The management of back pain by general practitioners does not match the guidelines, but there is little evidence from general practice for many of the recommendations, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 32 publications
1
64
0
2
Order By: Relevance
“…It has concentrated on availability of services 3 and GPs' self-reported management of the condition, comparing results against guideline best practice. 4,5 The results from these surveys are conflicting.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has concentrated on availability of services 3 and GPs' self-reported management of the condition, comparing results against guideline best practice. 4,5 The results from these surveys are conflicting.…”
Section: Introductionmentioning
confidence: 93%
“…4 In contrast, Little et al, 5 who also conducted a crosssectional postal questionnaire of 236 GPs (70% response rate) in one South West health district, compared GPs' reported management of back pain with the 1994 guidelines. 6 They reported that many GPs did not routinely perform recommended examinations or give advice about exercise and everyday activities.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines can be used to improve the quality of care or to ration the use of expensive treatments. There have also been numerous recommendations on how guidelines should be produced 14 together with examples of problems in their implementation in routine practice; for example the difficulty in implementing guidelines for the management of back pain in primary care 15 . By contrast, setting criteria for embarking on a particular type of therapy or undertaking a specific procedure may be helpful in improving the overall standard of care.…”
Section: Guidelines For Treatmentmentioning
confidence: 99%
“…Current guidelines, most of which have been recently introduced, aim at reducing the number of people with chronic pain and disability. Research shows that considerable change is needed to implement the guidelines fully (49,50), but also that the availability of recommended back pain services increased after the introduction of guidelines in the United Kingdom (51). Therefore, we can expect that, as guidelines become better implemented, the number of people with chronic pain and disability will decrease.…”
Section: Future Developmentsmentioning
confidence: 99%